Search for heavy long-lived charged particles with the ATLAS detector in pp collisions at root s=7 TeV - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
A search for long-lived charged particles reaching the muon spectrometer is performed using a data sample of 37 pb-1 from pp collisions at √s=7 TeV collected by the ATLAS detector at the LHC in 2010. No excess is observed above the estimated background. Stable τ̃ sleptons are excluded at 95% CL up to a mass of 136 GeV, in GMSB models with N5=3, mmessenger=250 TeV, sign(μ)=1 and tanβ=5. Electroweak production of sleptons is excluded up to a mass of 110 GeV. Gluino R-hadrons in a generic interaction model are excluded up to masses of 530 GeV to 544 GeV depending on the fraction of R-hadrons produced as g̃-balls. © 2011 CERN.